![\left \{{{x^2+3xy=4} \atop {4y^2+xy=5}} \right. \left \{{{x^2+3xy=4} \atop {4y^2+xy=5}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%7B%7Bx%5E2%2B3xy%3D4%7D%20%5Catop%20%7B4y%5E2%2Bxy%3D5%7D%7D%20%5Cright.)
сложим первое и второе:
x²+4xy+4y²=9;
(x+2y)²=9;
x+2y=-3; 3; Оба полученных варианта подставим в первое уравнение системы:
1) x=-2y-3;
4y²+(-2y-3)y=5
4y²-2y²-3y=5;
2y²-3y-5=0;
D=9+4*2*5=7²;
y1=(3+7)/4=2,5;
y2=(3-7)/4=-1;
x1=-2y-3=-5-3=-8;
x2=-2y-3=-2-3=-5;
2) x=3-2y;
4y²+(3-2y)y=5;
2y²+3y-5=0;
D=9+4*2*5=7²;
y3=(-3+7)/4=1;
y4=(-3-7)/4=2,5;
x3=3-2y=3-2=1;
x4=3-2y=3-5=-2;
(-8;2,5);(-5;-1);(1;1);(-2;2,5);